2017
DOI: 10.1002/cb.1668
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing, choice freedom, and duration judgments in choice making

Abstract: This paper examines (a) whether people are less accurate in judging choice time as choice tasks involve more choice options, more choice information, or a combination of both and (b) whether people with a higher tendency to look for the best option in choice making (maximizers) have less accurate duration judgments of choice time as compared to people who are more easily settling for a choice outcome that is satisfactory (satisficers). A multilevel analysis is used to explore the relationships of interest usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(135 reference statements)
1
5
0
Order By: Relevance
“…Building on the findings of previous studies (see Misuraca and Teuscher 2013;Rogge 2017), our research contributes to the maximization literature by further investigating the underlying mechanism of the relationship between maximization and time estimation. Our work delves into the realm of maximization from a memory perspective, revealing an interesting phenomenon: Maximizers experience a memory decay for special (or low commonality) information during the decision-making process.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Building on the findings of previous studies (see Misuraca and Teuscher 2013;Rogge 2017), our research contributes to the maximization literature by further investigating the underlying mechanism of the relationship between maximization and time estimation. Our work delves into the realm of maximization from a memory perspective, revealing an interesting phenomenon: Maximizers experience a memory decay for special (or low commonality) information during the decision-making process.…”
Section: Discussionmentioning
confidence: 88%
“…Previous research has demonstrated that people are sensitive to time costs, and most decisional behaviors are strongly affected by time estimation (e.g., Ackerman and Gross 2003; Mantel and Kellaris 2003; Rogge 2017). However, previous work has largely ignored the role of time estimation in maximizers' excessive investment of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the site requires them to "dig deeper," then they might very well quit the site. The second type, Optimizers, will seek comprehensive information and will leave if such information is not available (Mittal, 2016, Rogge, 2017. In contrast, Balanced diligents will seek information on important dimensions but without having to spend exorbitant effort.…”
Section: Shopper Needs Skills and Personalitymentioning
confidence: 99%
“…A greater number of options increase the perceived cost of lower satisfaction with the choice (Szrek, 2017). Rogge (2017) also stated that the quality of the choice also decreases with a higher number of options. Chernev, Böckenholt, and Goodman (2015) argued that a greater variety of options may lead to the postponement of the choice, higher probability of change and to a bias toward easily justifiable choices.…”
Section: Rege 262mentioning
confidence: 99%